تعلیم نسواں اور حضرت عائشہ کی تعلیمات و کردار، عصر حاضر کے تناظر میں تجزیاتی مطالعہ: Role of Hazrat Ayesha (R.A.W) in women’s education (Analytical Study in light of contemporary era) - Fakhra Tehseen; Dr. Muhammad Arshad (jihat-ul-islam, 2021)
Islam is a practical religion. It started preaching its teaching under the enlightenment of knowledge Instead of darkness of ignorance. In contrast to other religion, Islam considers men and women (both) as equal pioneers of civilized society. The significant feature of Islam is that it stresses education as mandatory elements for both of man and woman uplift the society۔ The role of Hazrat Ayesha (R.A.W) in uplifting women’s education in society and make them literal is beyond any doubt .She is considered as first (women fakiha )in the history of Islam equipped with concrete Islamic knowledge .Her colleagues and friends used to consult her whenever confronted with any problem of Shariya .Imam Zahri revealed that Hazrat Ayesha (R.A.W) has much more knowledge of Islamic Shariya then the sum of the knowledge of all the “Azwaje-Mutaharat .”Hazrat Ayesha was kind, wise and intelligent woman. She addressed the problems of women elegantly even after the departure of Hazrat Muhammad (S.A.W).She convincingly taught them the solution of Islamic problems especially relating to women in the light of Holy Quran and Sunnah, She provided them self-confidence and awareness about their legal rights .She guided them in solution their problems regarding family matters۔. She nourishes then, moral values and guided them in matters of social welfare and Jihad .She proved that a woman can contribute to solve all the problems of society by keeping their selves under Hijab, she arranged numbers of meetings of women with Hazrat Muhammad( S.A.W) in which women can directly ask questions to him(S.A.W). Women of present era can consider the life of Hazrat Ayesha as a role model. The purpose of presenting this article is how contemporary women can get benefit from the teaching and lifestyle of Hazrat Ayesha (R.A.W) and play a revolutionary part in changing the society positivity. At the end of article pertain purposed are made for women of present society which may be helpful in uplifting and repairing the moral deteriorative society.